Loaded and Unloaded Sit-to-Stand Strengthening Exercises Effect to Gross Motor Function Measure in Spastic Diplegia Cerebral Palsy Patients - Imran Safei; Marina A. Moeliono; Tertianto Prabowo (Faculty of Medicine Universitas Padjadjaran, 2016)
Objective: To examine sit-to-stand and loaded sit-to-stand exercises effect in standing, walking, and running dimensions of gross motor function measure (GMFM) in spastic diplegia cerebral palsy (SDCP) patients.Methods: This study was conducted in the period of May to October 2014 and included 24 children with SDCP as the subjects. The methods used in the study were interventional study with randomized controlled trial, and investigation of CP before and after the exercise intervention. The subjects were divided into two groups, sit-to-stand exercise group and loaded sit-to-stand exercise group. Results: The results showed that the increase of standing, walking, and running dimension scores of GMFM in the loaded group were higher (standing dimension score 12.00 vs 11.08 and walking and running dimensions 13.58 vs 13.42) compared to the unloaded group.Conclusions: Both sit-to-stand and loaded sit-to-stand exercise groups do not show significant differences in improving motor skills in standing, walking, and running dimensions of GMFM. Children with SDCP may receive the exercise to improve their motor skills in mobility aspects, such as standing, walking, and running. Keywords: Cerebral palsy, gross motor function measure, rehabilitation, sit-to-stand exercise DOI: 10.15850/ijihs.v4n1.680